P115 Monitoring faecal calprotectin at 3 months post-surgery is useful to predict further postoperative endoscopic recurrence in Crohn's disease. (25th January 2019) - Veyre, F; Nancey, S; Meunier, C; Roblin, X; Cuerq, C; Mialon, A; Danion, P; Chauvenet, M; Flourie, B; Boschetti, G
Abstract: Background: Most of the patients with Crohn's diseases (CD) underwent surgery and the risk of postoperative recurrence remains high. An ileocolonoscopy is recommended within the first year post-surgery to detect postoperative endoscopic recurrence (POR) that precedes clinical recurrence. Faecal Calprotectin (fCal) monitoring within the first year post-surgery is useful to predict POR and could avoid performing some colonoscopies. However, the usefulness of an early postoperative monitoring of fCal as soon as 3 months post-surgery to detect the occurrence of further POR within 1 year after surgery remains unknown. Methods: Stool samples were collected 3 months post-surgery in a cohort of 55 consecutive CD patients who had undergone an ileocolonic resection to measure fCal concentrations by an immunoenzymatic assay (Bühlmann). An ileocolonoscopy was performed within the first year post-surgery and endoscopic recurrence, graded by the Rutgeerts score (POR defined as Rutgeerts >i1) was assessed. The performance, sensitivity, specificity, predictive values of fCal levels to predict further POR as well as the optimal cut-off point capable to predict POR has been determined by ROC curves. Results: At 3 months post-surgery, the mean fCal levels were significantly higher in patients with endoscopic recurrence, when compared with those in endoscopic remission (204.9 µg/g; 95% CI [124–660 µg/g] vs. 102.9 µg/g [61–207 µg/g] respectively; p = 0.0071). Based on the AUROC, the accuracy of fCal measured at 3 months post-surgery was 0.712. The respective sensitivities, specificities, positive and negative predictive values according to various cut-off points are summarised in Table 1. The fCal value of 65 µg/g was the best cut-off point to accurately distinguish the patients who will further experience a POR from those who will stay in endoscopic remission, and this could allow avoiding around 20% of colonoscopies given the high NPV of fCal in this setting. Conclusions: The present study reports the usefulness of monitoring fCal as soon as 3 months post-surgery to predict accurately POR in CD patients. FCal levels below 65 µg/g at 3 months post-surgery could help making decision to avoid performing an ileocolonoscopy within 1 year post-surgery.